Dynamic Key Matrix of Hill Cipher Using Genetic Algorithm - Andysah Putera Utama Siahaan (Institute of Advanced Engineering and Science, 2017)
The matrix in Hill Cipher was designed to perform encryption and decryption. Every column and row must be inserted by integer numbers. But, not any key that can be given to the matrix used for the process. The wrong determinant result cannot be used in the process because it produces the incorrect plaintext when doing the decryption after the encryption. Genetic algorithms offer the optimized way to determine the key used for encryption and decryption on the Hill Cipher. By determining the evaluation function in the genetic algorithm, the key that fits the composition will be obtained. By implementing this algorithm, the search of the key on the Hill Cipher will be easily done without spending too much time. Genetic algorithms do well if it is combined with Hill Cipher.